AN ANALYSIS OF STUDENTS’ SPEAKING ABILITY IN ENGLISH CONVERSATION CLUB (ECC) PROGRAM AT THE 3rd SEMESTER - Rica Hiana Shinta Hia; Herdi Herdi; M. Fadhly Farhy Abbas (Lectura : Jurnal Pendidikan, 2016)
This research is based on students’ speaking ability who had followed the EnglishConversation Club (ECC) program especially for the third semester of English Department. Thepurpose of this study was to analyze the students’ speaking ability at the 3rd semester in the EnglishConversation Club FKIP UNILAK Pekanbaru. The type of the research was mixed method in typeof explanatory design. The number of participant was 53 students. The researcher used twoinstruments, those were test and interview. In analyzing the data, it used in descriptive statistics.The result of the analysis showed that the average score of 3rd semester students’ speaking abilitywas 45.42. It can be concluded that the students’ speaking ability was categorized into failed . Thescore of Standard Deviation was 7.02, Variance was 49.30, and Range was 36 points . It meansthat the students’ speaking ability was homogeneous. According to the Z-Score, it can be seen that49.06% students’ ability was higher than average and 50.94% students ability was below theaverage. In conclusion, the students’ ability in learning speaking English was failed, it had beenaffected by some factors, those were lack of vocabulary, grammar and motivation. It was supportedby the interview, eventhough the students’ perception to English Conversation Club (ECC)program was positive, but in fact, the students’ frequency to speak English was seldom, they wereless practice speaking English everyday.